2022
DOI: 10.1177/08927057221137805
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hygrothermal ageing on the novel infusible thermoplastic resin reinforced with quadriaxial non-crimp glass fabrics

Abstract: Elium® is a novel liquid Methylmethacrylate thermoplastic (TP) matrix that can be cured at room temperature. Elium® resin provides the properties of TP polymer composites and is a competitive alternative to epoxy-based composites. In this work, a quadriaxial non-crimp (NC) glass fabric/Elium® based polymer composites were manufactured using vacuum assisted resin transfer moulding (VaRTM). The static mechanical properties of these composites were evaluated under the tensile and flexural loads. Further, interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Agreement in the flexural behaviour of GFRP3 was found with the work reported by Nash et al [38], which studied the behaviour of UD glass/acrylic liquid thermoplastic (namely Elium 150) composites at 35 • C hygrothermal ageing for 28 days and revealed a 17.3 and 0.4% loss of flexural strength and modulus, respectively. On the other hand, Bandaru et al [39] revealed an approximately 59 and 62% decline in the flexural strength and modulus, respectively, after 60 days of hygrothermal ageing at 60 • C for the non-crimp quadriaxial glass fibre-reinforced acrylic (Elium 150) thermoplastic composites. Here, the drops in flexural strength and modulus were 9 and 55% higher, respectively, than in GFRP3 composites that were aged at 60 • C for 56 days in the current work.…”
Section: Moisture Uptake (%)mentioning
confidence: 99%
“…Agreement in the flexural behaviour of GFRP3 was found with the work reported by Nash et al [38], which studied the behaviour of UD glass/acrylic liquid thermoplastic (namely Elium 150) composites at 35 • C hygrothermal ageing for 28 days and revealed a 17.3 and 0.4% loss of flexural strength and modulus, respectively. On the other hand, Bandaru et al [39] revealed an approximately 59 and 62% decline in the flexural strength and modulus, respectively, after 60 days of hygrothermal ageing at 60 • C for the non-crimp quadriaxial glass fibre-reinforced acrylic (Elium 150) thermoplastic composites. Here, the drops in flexural strength and modulus were 9 and 55% higher, respectively, than in GFRP3 composites that were aged at 60 • C for 56 days in the current work.…”
Section: Moisture Uptake (%)mentioning
confidence: 99%